МАВЗОЛЕИ АЙША-БИБИ И БАБАДЖИ-ХАТУН: ИССЛЕДОВАНИЯ, РЕСТАВРАЦИОННЫЕ РАБОТЫ И АТЕИСТИЧЕСКАЯ ПРОПАГАНДА СОВЕТСКОГО ПЕРИОДА - Сапатаев, S. A.; Куралова, Z. S.; Жолдасулы, Т. (Journal of history, 2025)
The Aisha Bibi and Babaji-Khatun Mausoleums are unique examples of Islamic architecture from the XI-XII centuries and hold a significant place in the historical and cultural heritage of Kazakhstan. This article analyzes the study and restoration of these mausoleums, as well as the impact of Soviet-era atheistic policies on their preservation. The aim of the study is to reveal the historical and architectural features of the mausoleums, assess the effectiveness of Soviet restoration methods, and explore the consequences of atheistic propaganda. The research utilizes documents from the State Archive of Zhambyl Region, the Central State Archive of Cinema, Photo, and Audio Documents of the Republic of Kazakhstan, and the Scientific Archive of the A.Kh. Margulan Institute of Archaeology. A historical-comparative analysis of archival data provided deeper insights into the cultural and historical significance of the mausoleums. The article examines the organizational and technical limitations of Soviet-era restoration efforts, as well as the influence of Soviet totalitarian ideology on the spiritual and cultural role of these mausoleums. Particular attention is given to the architectural features, restoration methods, and outcomes related to the Aisha Bibi and Babaji-Khatun mausoleums, emphasizing the richness and uniqueness of Kazakhstan’s cultural heritage. The study’s findings demonstrate the need for systematic and scientifically grounded approaches to preserving the historical and cultural value of these mausoleums. This article contributes to research in the field of cultural heritage preservation in Kazakhstan and can serve as a methodological foundation for future restoration and scholarly projects.